Quantifying catchment-scale coarse sediment dynamics in British rivers - Parker, Chris (2010)
It has become increasingly clear that river channel sediment dynamics must be taken into account within British flood risk management because changes in channel morphology resulting from sediment transfer can have an impact on channel flood capacity. It is also recognised that an understanding of catchment-scale sediment dynamics is desirable with respect to many other aspects of river management. However, despite this recognition, application of existing approaches that account for coarse sediment dynamics has been limited within British river management. Based on these considerations, this study aims to develop and substantiate a new approach that quantitatively accounts for catchment-scale coarse sediment dynamics in British rivers. These research efforts contribute to the activity of the Flood Risk Management Research Consortium (http://www.floodrisk.org.uk/) A review of the availability and accuracy of data sources useful to considerations of coarse sediment dynamics reveals that only discharge, channel slope, and channel width can be represented widely at the catchment-scale. As a result, none of the approaches currently available to account for coarse sediment dynamics were found to be both scientifically robust and practically applicable at the catchment-scale. This leads to the conclusion that the most suitable approach to account for coarse sediment dynamics at the catchment-scale in British rivers is a reach-based sediment balance model, using no more than slope, width and discharge data. A new reach-based sediment balance model, ST:REAM (Sediment Transport: Reach Equilibrium Assessment Method), is developed. It has several unique features including: representation of the entire catchment network; automatic delineation of the catchment network into functional reaches using a zonation algorithm; application of a new general formula for the prediction of bed surface material transport rate; and adoption of an assumption that makes it unnecessary to collect bed material size data. The outputs from ST:REAM are in the form of predicted Capacity Supply Ratios which compare the annual mass of sediment predicted to enter a reach with the annual mass of sediment predicted to leave it. Initial assessment of ST:REAM using two test catchments shows that it can produce a reasonable representation of observed, broad-scale sediment dynamics. The accuracy of its predictions decreases when attempting to incorporate downstream variability in bed material size into the model, and scale issues are encountered when attempting to increase the resolution at which reaches are identified by the zonation algorithm. ST:REAM has many potential applications within river management, but it is of most value when providing a broad-scale picture of predicted reach sediment balances throughout the drainage network. As well as the practical applications of ST:REAM, the research contained within this thesis has important theoretical implications, relating both to the insights it provides on catchment-scale sediment dynamics in particular and methodological and foundational developments in the field of sediment studies more generally.